A case of foreign body aspiration mimicking asthma in adult - Jamani, Nurjasmine Aida; Abdul Azih, Muhammad Naimmuddin; Haroon, Raihanah; Mohd Shaari, Nur Shairah (UPM Press, 2023)
Foreign body aspiration is uncommon in adults who have no known risk factors such as mental retardation, poor dentition, or advanced age. Adults with foreign body aspiration are commonly misdiagnosed with bronchial asthma, however, does not respond to standard bronchodilator treatment. A thorough history-taking, focused physical examination and a high index of suspicion is crucial in making the correct diagnosis. This paper reports an interesting case of a 41- year-old woman with an undetected 10-year long foreign body aspiration which was misdiagnosed as bronchial asthma.